Information (maps, projects) collected for safety space management - Kocur-Bera, Katarzyna (International Conference “Environmental Engineering”, 2017)
The main aim of the study is to analyse the maps and projects which inform us about locations at risk of extreme weather events and other hazards to the space. In the last decade, research into hazards has become an area of interest to many projects under implementation. During their implementation, a lot of information with a different scope, accuracy and scale is obtained. The projects and maps under study provide valuable information for various levels of space management and planning as well as for crisis management. For the implementation of research aims, an analysis and synthesis of the obtained materials concerning the maps and projects were used. The results indicate that the gathered information does not always fulfil the needs of local governments. In spatial planning, information should refer to a cadastral parcel or real estate; however, certain projects and maps are not accurate enough and have a rather global coverage, which makes them useless for the purposes of spatial planning. To this end, an analysis and synthesis of the obtained materials concerning the maps and projects were used.
Keywords: management of the safe space; information; project; maps